A Quasi-Fast Solver for Weakly Singular Integral Equations of the Second Kind. (18th May 2020) - Rehman, Sumaira; Pedas, Arvet; Vainikko, Gennadi
Abstract: We discuss bounds of quasi-fast or fast solving weakly singular Fredholm integral equation of the second kind. We modify the method presented in Rehman et al. (2018).